Mindfulness Parenting Strategies in Building Positive Family Parenting at Al-Ikhlas Konggo Kindergarten, Deli Serdang Regency - Munisa; Dwi Utami, Rahayu (JOLADU: Journal of Language Education, 2023)
Children who were cared for by applying mindfulness parenting strategies in building positive parenting give more to their friends, then their thinking was broader and more mature, able to control their emotions, but if the child was angry, then it was greater with his friends who got angry first. Children like this had a positive influence on the environment and their friends, children were respected and many of their friends like to be with them, not even just children, parents were also sympathetic to children because the child's character reflects good behavior. The results of the study show that the mindfulness parenting strategy in building positive parenting is that parents show affection for themselves and their children, parents want to listen with full attention, self-regulation in parenting and aspects of affection for themselves and children. Parents who have a mindfulness parenting strategy in building positive parenting will avoid stress, social anxiety, increase satisfaction and feel calm. Obstacles in implementing mindfulness parenting strategies in building positive parenting, there are obstacles, namely the difficulty in managing emotions for early childhood who are not yet emotionally stable. then the obstacle faced by parents is the difficulty of managing time between parenting and work.